The Humanistic Art Perspective: Ono Saseo's Portrayal of Indonesia - Purnomo, Antonius Rahmat Pujo (KIRYOKU, 2024)
Ono Saseo was a Japanese cartoonist who was recruited as a member of the Japanese Army's Propaganda Division and sent to Java from 1942 to 1945. During his service in Indonesia, he created hundreds of artworks for both military and personal purposes. The purpose of this research is to understand Ono Saseo's views and humanistic values towards the Indonesian people. The research method used is qualitative research, examining Ono Saseo's writings and drawings to uncover the meanings contained within. Additionally, the researcher also examined the opinions of other artist who lived during the same period as Ono Saseo to gain a clearer depiction of Ono. The results of the research show that not all of Ono's drawings published in the Japanese mass media in Indonesia depict elements of Japanese foreign political conflicts against the West, but rather, most of them portray the joyful atmosphere and the harmony of the Indonesian people and Western. Ono's significant attention to the Indonesian society, natural environment, and other nations residing in Indonesia demonstrates his deep humanistic side, both as an intellectual and as a human being.